THE INFLUENCE OF EXPERIENTIAL MARKETING, SATISFACTION ON CUSTOMER LOYALTY: A STUDY ON THE HOTEL INDUSTRY IN INDONESIA - Muh. Syaiful Saehu; Bahtiar Efendi; Teguh Setiawan Wibowo; Aat Ruchiat Nugraha (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This quantitative research investigates the relationship between Experiential Marketing (X1), Satisfaction (X2), and Customer Loyalty (Y) in the hotel industry. Data was collected through a questionnaire via goggle form with questions and statements related to the third variable. The research sample was selected based on hotels with a -+ 4 star rating. The data analysis method used multiple linear regression, T test, and F test using SPSS software. The research results revealed: 1). Experiential Marketing (X1) and Satisfaction (X2) have a significant positive influence on Customer Loyalty (Y) in multiple linear regression analysis. 2). The T test shows that both X1 and X2 separately have a significant effect on Customer Loyalty with the appropriate level of significance. 3). The results of the F test state that X1 and X2 together have a significant effect on Customer Loyalty. This research underscores the importance of creating engaging experiences for customers and ensuring their satisfaction to maintain and increase customer loyalty in the hotel industry. The implications of this research strengthen the role of these two variables in competition in the hotel industry and customer retention strategies.